1986
DOI: 10.1103/physrevc.33.176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of entrance channel and compound nucleus in the fusion cross sections for28Si+

Abstract: In order to study the physics responsible for a hmitation in angular momentum in heavy-ion fusion reactions, fusion cross sections for the reactions 2sSi+isSi, '60+~Ca, 3tS+s Si, and ' C+' Cr have been measured at several incident energies covering lower and higher energy regions by detecting the yields of the fusion-evaporation residues. The limiting angular momenta for fusion are extracted from the measured fusion cross sections and compared with calculations based upon several models. Through the systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 25 publications
6
21
0
Order By: Relevance
“…From this systematic analysis, it can be observed that the magnitude of the quadrupole deformation that can be deduced for both 28,30 Siϩ 28,30 Si reactions is rather large: their parameter values are similar to the value obtained for the 32 Sϩ 27 Al reaction ͓9,19͔ but larger than the value corresponding to the 28 Siϩ 27 Al reaction ͓13͔. This leads to the striking conclusion that highly stretched configurations are required to account for the observed ␣-particle evaporation spectra.…”
Section: Reactionmentioning
confidence: 91%
“…From this systematic analysis, it can be observed that the magnitude of the quadrupole deformation that can be deduced for both 28,30 Siϩ 28,30 Si reactions is rather large: their parameter values are similar to the value obtained for the 32 Sϩ 27 Al reaction ͓9,19͔ but larger than the value corresponding to the 28 Siϩ 27 Al reaction ͓13͔. This leads to the striking conclusion that highly stretched configurations are required to account for the observed ␣-particle evaporation spectra.…”
Section: Reactionmentioning
confidence: 91%
“…Several other data sets for the 28Si + 28Si system exist [31][32][33] and indeed one of the aims of Aguilera et al [33] was to search for oscillations in this system. Unfortunately, they were unable to conclude the existence of structures within the 3% statistical error in their experiment.…”
Section: Heavier Systemsmentioning
confidence: 99%
“…His rule is based upon a microscopic resonating group method within a two-center harmonic-oscillator shell model. Essentially the barrier for even partial waves is deemed to be higher (or lower) than that for odd partial waves if the quantity _ (_iyW Y[ ni i: valence (32) is positive (or negative). In both of our cases Acore is even.…”
Section: B 12c + L3c Fusion Reactionmentioning
confidence: 99%
“…It is difficult to calibrate the M3Y+repulsion interaction to the 28 Si+ 28 Si data by Gary and Volant [16] because they cover a relatively small range of energies. Fortunately, there is another data set by Nagashima et al [17] which covers a much broader range of energies, and the high energy data by Vineyard et al [18] are also very valuable because they determine a limiting or critical angular momentum for fusion, which is about L c = 38h.…”
Section: Applications To Heavier Systemsmentioning
confidence: 99%